STRATEGI IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN PAI DALAM MENINGKATKAN KEMAMPUAN KOGNITIF SISWA - Gusri, Fauziah; Putra, Rudi Yongki Nanda; Fadriati, Fadriati; Suryana, Ermis (STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
This study points to identify and analyze the usage strategy of the Autonomous Educational programs in Islamic Devout Instruction (PAI) learning in rudimentary schools. Employing a subjective approach, this investigate includes collecting information through interviews, perceptions, and documentation from PAI instructors in a few schools that have actualized the Free Educational programs. The comes about of the think about appear that the usage of the Autonomous Educational modules in PAI prioritizes student-centered learning, with a center on character advancement and life abilities through topical and venture approaches. Procedures that have been effectively executed incorporate the utilize of intelligently dialog strategies, the utilize of innovation in learning, and the integration of devout values in different exercises. Be that as it may, the ponder moreover recognized a number of challenges, such as a need of preparing for instructors and constrained supporting assets. Based on these discoveries.